Analisis Penerapan Model Problem Based Learning Untuk Meningkatkan Kemampuan Berpikir Kreatif Siswa pada Materi Pythagoras - Rahmanpematuir Hidayat; Astri Wahyuni (MUARA PENDIDIKAN : Jurnal Ilmiah Ilmu Pendidikan & Sosial Humaniora, 2026)
This study aims to analyze the implementation of the Problem Based Learning (PBL) model in improving students' creative thinking skills in learning the Pythagorean theorem. The research employed a qualitative literature review approach. Data were collected through documentation studies of relevant scientific articles obtained from Google Scholar and SINTA-indexed journals published within the last five years. Three main articles were selected and analyzed based on the learning model, mathematical approach, learning materials, and research findings. The results indicate that the implementation of Problem Based Learning has a positive effect on students' creative thinking skills through problem-solving activities, discussions, and idea exploration. Scientific approaches help students understand mathematical concepts and develop logical thinking skills. However, analytical and synthetic approaches were found to be the most suitable for Pythagorean learning because they encourage students to analyze problems, develop multiple solution strategies, and enhance creativity in mathematical thinking. Therefore, the Problem Based Learning model supported by analytical and synthetic approaches can serve as an effective alternative for improving students' creative thinking skills in learning the Pythagorean theorem.